Electrode material and preparation method thereof, secondary battery and electrode

By combining and modifying different carbon sources, a carbon-containing powder was prepared, which solved the problem of difficulty in taking into account the energy density and circulation performance of sodium ion batteries in the prior art, and achieved high compaction density and high capacity electrode materials.

CN119890299APending Publication Date: 2025-04-25SHENZHEN BTR NEW ENERGY TECH RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411998871.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the prior art, the main technical bottleneck of hard carbon used in sodium ion batteries is the difficulty in taking into account both energy density and cycling performance.

Method used

By combining with different types of carbon sources, a carbon-containing powder was prepared, with a conductivity of 36S/cm to 41S/cm, a nitrogen mass percentage of 0.2wt% to 0.9wt%, and a closed pore volume of 0.03cm3/g to 0.07cm3/g. The method of preparing the electrode material includes modifying the first carbon source, then mixing with the second carbon source for pretreatment, oxidation treatment and sintering treatment to obtain a carbon-containing powder.

Benefits of technology

This electrode material exhibits high compaction density, high capacity, high first-time efficiency and good magnification and cycling performance in sodium ion batteries, and is suitable as a high-performance hard carbon anode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890299A_ABST
    Figure CN119890299A_ABST
Patent Text Reader

Abstract

The invention discloses an electrode material and a preparation method thereof, a secondary battery and an electrode, and the electrode material comprises: carbon-containing powder; wherein the value range of the electric conductivity of the carbon-containing powder is 36 S / cm to 41 S / cm; the value range of the mass percent of the nitrogen element in the carbon-containing powder is 0.2 wt%-0.9 wt%; the value range of the closed pore volume of the carbon-containing powder is 0.03 cm < 3 > / g to 0.07 cm < 3 > / g. The invention has the beneficial effect of providing the electrode material of which the performance is improved by compounding different types of carbon sources, the preparation method thereof, the secondary battery and the electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of secondary batteries, and in particular, relates to an electrode material and a preparation method thereof, a secondary battery, and an electrode. Background Art

[0002] Compared with lithium-ion batteries, sodium-ion batteries have the characteristics of high safety, low temperature resistance, and fast charging. They are considered to be the best complementary or alternative power source for lithium-ion batteries and have very broad application prospects in the fields of two-wheeled vehicles, energy storage, start-stop power supplies, etc. Hard carbon materials are considered to be the most commercially promising sodium battery negative electrode materials due to their high capacity, good conductivity, stable structure, and high output voltage.

[0003] In some related technologies, the main technical bottleneck of using hard carbon in sodium-ion batteries is the difficulty in balancing energy density and cycle performance. Summary of the invention

[0004] In view of this, the present application provides an electrode material and a preparation method thereof, and a secondary battery, aiming to solve the aforementioned technical problems.

[0005] In a first aspect, an embodiment of the present application provides an electrode material for use in a sodium ion battery, the electrode material comprising: a carbonaceous powder;

[0006] The conductivity of the carbon-containing powder is in the range of 36S / cm to 41S / cm; the mass percentage of nitrogen in the carbon-containing powder is in the range of 0.2wt% to 0.9wt%; the closed pore volume of the carbon-containing powder is in the range of 0.03cm 3 / g~0.07cm 3 / g.

[0007] Optionally, in some embodiments of the present application, the mass percentage of nitrogen in the carbon-containing powder ranges from 0.4 wt % to 0.7 wt %.

[0008] Optionally, in some embodiments of the present application, the 3T powder compaction density of the carbon-containing powder is in the range of 0.95 g / cm 3 ~1.05g / cm 3 ;

[0009] And / or, the carbon interlayer spacing of the electrode material ranges from 0.37 nm to 0.39 nm;

[0010] And / or, the median particle size of the carbon-containing powder is in the range of 3 μm to 15 μm;

[0011] And / or, the specific surface area of ​​the carbon-containing powder is in the range of 2.0 m 2 / g~10.0m2 / g.

[0012] In a second aspect, an embodiment of the present application provides a method for preparing an electrode material, comprising:

[0013] The preparation method comprises:

[0014] Modifying the first carbon source to obtain a modified carbon source;

[0015] The modified carbon source and the second carbon source are mixed and pretreated to obtain a first precursor;

[0016] The first precursor is subjected to oxidation treatment to obtain a second precursor;

[0017] sintering the second precursor to obtain a carbonaceous powder as the electrode material;

[0018] The conductivity of the carbon-containing powder is in the range of 36S / cm to 41S / cm; the mass percentage of nitrogen in the carbon-containing powder is in the range of 0.2wt% to 0.9wt%; the closed pore volume of the carbon-containing powder is in the range of 0.03cm 3 / g~0.07cm 3 / g.

[0019] Optionally, in some embodiments of the present application, the first carbon source includes a plant carbon source.

[0020] Optionally, in some embodiments of the present application, the plant carbon source is selected from at least one of coconut shells, almond shells, pistachio shells, macadamia shells, date shells, chestnut shells, hazelnut shells, peanut shells, walnut shells, peach shells, cotton, wood, bamboo, straw, and lignin.

[0021] Optionally, in some embodiments of the present application, the second carbon source includes a carbon source having a melting point and / or a softening point.

[0022] Optionally, in some embodiments of the present application, the carbon source having a melting point and / or a softening point includes an organic polymer carbon source and / or a sugar carbon source.

[0023] Optionally, in some embodiments of the present application, the organic polymer carbon source is selected from at least one of phenolic resin, epoxy resin, melamine resin, polyfurfuryl alcohol, polyaniline, furfural resin, polyethylene glycol, polyethylene oxide, polyvinylidene fluoride, acrylic resin or polyacrylonitrile; and / or,

[0024] Wherein, the carbohydrate carbon source is selected from at least one of starch, glucose, sucrose, maltose, lactose, fructose, cellulose and galactose.

[0025] Optionally, in some embodiments of the present application, the step of modifying the first carbon source to obtain a modified carbon source comprises:

[0026] performing a first oxidation treatment on the powder of the first carbon source to obtain a first oxidation product;

[0027] The first oxidation product is subjected to a first reduction treatment to obtain the modified carbon source.

[0028] Optionally, in some embodiments of the present application, the first oxidant used for the first oxidation treatment is selected from at least one of nitric acid and an acid solution of nitrate; the acid solution of nitrate is obtained by dissolving nitrate in an acid solution; the nitrate includes at least one of sodium nitrate, potassium nitrate, magnesium nitrate, zinc nitrate, iron nitrate, cobalt nitrate, nitrate, ammonium nitrate, calcium nitrate, lead nitrate, and cerium nitrate; the acid solution includes one or a combination of at least two of hydrochloric acid, hydrofluoric acid, phosphoric acid, and sulfuric acid;

[0029] And / or, the oxidation temperature of the first oxidation treatment ranges from 60°C to 80°C;

[0030] And / or, the oxidation time of the first oxidation treatment ranges from 3h to 24h;

[0031] And / or, the mass concentration of the nitric acid is 0.5wt% to 5.0wt%; the mass proportion of nitrate in the nitrate acid solution is 0.5wt% to 5.0wt%; the ratio of the mass of the first carbon source to the mass of the solution of the first oxidant is in the range of 2 to 20.

[0032] Optionally, in some embodiments of the present application, the first reducing agent of the first reduction treatment is selected from at least one of formic acid, ammonium formate, hydrazine hydrate, sodium sulfide, and sodium thiosulfate;

[0033] and / or, the first catalyst of the first reduction treatment is selected from soluble salts of transition metal elements;

[0034] And / or, the temperature of the first reduction treatment ranges from 60°C to 80°C;

[0035] And / or, the reduction time of the first reduction treatment ranges from 3h to 10h;

[0036] And / or, the mass ratio of the first oxidation product, the first reducing agent, the first catalyst, and the solvent is in the range of 1:(0.3-3):(0.1-0.2):(1.5-10);

[0037] And / or, the solvent is at least one of tetrahydrofuran, ethanol, benzene, isopropanol and pure water.

[0038] Optionally, in some embodiments of the present application, wherein the modifying the first carbon source to obtain a modified carbon source further comprises:

[0039] The product of the first oxidation treatment is centrifuged or filtered, washed to a first pH value, and then dried;

[0040] and / or, centrifuging or filtering the product of the first reduction treatment, washing it to the second pH value, and then drying it;

[0041] Among them, the first pH value range is 3-7; the second pH value range is 3-7.

[0042] Optionally, in some embodiments of the present application, the mixing of the modified carbon source and the second carbon source and then pre-treating to obtain the first precursor comprises:

[0043] The modified carbon source and the second carbon source are mixed and then heated and cured to obtain a cured product;

[0044] The solidified product is subjected to a pre-carbonization treatment to obtain a first precursor.

[0045] Optionally, in some embodiments of the present application, the heating temperature of the heating curing is in the range of 100° C. to 300° C.;

[0046] And / or, the heating time of the heating curing is in the range of 0.5h to 24h;

[0047] And / or, the pre-carbonization heating temperature is in the range of 450°C to 650°C;

[0048] And / or, the pre-carbonization heating time ranges from 0.5h to 24h;

[0049] And / or, the pre-carbonization atmosphere is an inert atmosphere or an oxygen-deficient atmosphere;

[0050] And / or, the inert atmosphere is selected from at least one of nitrogen atmosphere, argon atmosphere, neon atmosphere, helium atmosphere, xenon atmosphere, and krypton atmosphere;

[0051] And / or, the oxygen-deficient atmosphere is a gas atmosphere with an oxygen content of less than or equal to 1 wt %.

[0052] Optionally, in some embodiments of the present application, the pretreatment after mixing the modified carbon source with the second carbon source to obtain the first precursor further comprises:

[0053] After the modified carbon source and the second carbon source are mixed, the mixture is subjected to a pressing process before being heated, cured and pre-carbonized;

[0054] The mass ratio of the modified carbon source to the second carbon source is 1:(0.3-3.0);

[0055] The pre-carbonized product is crushed and sieved;

[0056] The pulverizing equipment used in the pulverizing process is selected from at least one of a ball mill, a jet mill, a mechanical pulverizer, and a roller mill;

[0057] and / or, the target median particle size of the pulverization process is 3 μm to 15 μm;

[0058] And / or, the mesh size of the sieve for the sieving process ranges from 30 mesh to 325 mesh;

[0059] And / or, the pressing pressure of the pressing process is in the range of 10 MPa to 20 MPa.

[0060] Optionally, in some embodiments of the present application, the pretreatment after mixing the modified carbon source with the second carbon source to obtain the first precursor further comprises:

[0061] Performing a purification process after the pulverization process;

[0062] Wherein, the purification process comprises:

[0063] The pulverized product is mixed with an acid solution and pure water in a certain mass ratio of 1:(0.1-1):(1.5-10), and after stirring for a preset time, solid-liquid separation is performed to obtain a solid product;

[0064] washing the solid product to a third pH value;

[0065] The acid solution is an aqueous solution of at least one selected from hydrochloric acid, hydrofluoric acid, nitric acid, phosphoric acid and sulfuric acid; and the third pH value ranges from 2.5 to 4.5.

[0066] Optionally, in some embodiments of the present application, the step of subjecting the first precursor to oxidation treatment to obtain the second precursor comprises:

[0067] performing a second oxidation treatment on the first precursor;

[0068] The atmosphere of the second oxidation treatment is an oxidizing atmosphere, which includes a carrier gas and an oxidizing gas, wherein the carrier gas is an inert gas, including any one of nitrogen, argon, neon, helium, xenon or krypton, or a combination of at least two thereof; the oxidizing gas is selected from at least one of oxygen, ozone, air and carbon dioxide, and the volume content of the oxidizing gas in the oxidizing atmosphere is 5%VOL to 30%VOL;

[0069] The temperature of the first oxidation treatment of the first precursor is 500° C. to 800° C.; the holding time of the first oxidation treatment is 1 h to 10 h.

[0070] Optionally, in some embodiments of the present application, in the step of sintering the second precursor to obtain a carbon-containing powder as the electrode material; the sintering temperature ranges from 1200°C to 1500°C; the sintering time ranges from 0.5h to 24h; the sintering atmosphere is an inert atmosphere, and the inert atmosphere is selected from at least one of nitrogen atmosphere, argon atmosphere, neon atmosphere, helium atmosphere, xenon atmosphere, and krypton atmosphere.

[0071] In a third aspect, an embodiment of the present application provides a secondary battery, comprising the aforementioned electrode material or the electrode material prepared by the preparation method.

[0072] In a fourth aspect, an embodiment of the present application provides a secondary battery, comprising the aforementioned electrode material, the electrode material obtained by the preparation method, or the aforementioned electrode.

[0073] The beneficial effects of the present application are: providing an electrode material with improved performance through the combination of different types of carbon sources and a preparation method thereof, a secondary battery, and an electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0074] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.

[0075] Figure 1 It is a schematic diagram of the main steps of the method for preparing the electrode material provided in some embodiments of the present application;

[0076] Figure 2 It is a schematic diagram of the main process of the method for preparing the electrode material provided in some embodiments of the present application;

[0077] Figure 3 is a side curve diagram of the specific capacity of the carbon-containing powder obtained in Example 1, Comparative Example 17 and Comparative Example 18;

[0078] Figure 4 is a normal temperature cycle performance curve of the carbon-containing powder obtained in Example 1, Comparative Example 17 and Comparative Example 18;

[0079] Figure 5 These are SEM photos and cross-sectional photos of the carbon-containing powders obtained in Example 1 (A, C) and Comparative Example 17 (B, D). DETAILED DESCRIPTION

[0080] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0081] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0082] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.

[0083] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0084] In the present application, "at least one" means one or more, and "plurality" means two or more. "One or more", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, a~b (i.e. a and b), a~c, b~c or a~b~c, where a, b, c can be single or multiple, respectively.

[0085] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0086] Reference Figure 1-2 As shown, in the first aspect, the embodiment of the present application provides an electrode material for use in a sodium ion battery, the electrode material comprising: a carbon-containing powder; wherein the conductivity of the carbon-containing powder ranges from 36S / cm to 41S / cm; the mass percentage of nitrogen in the carbon-containing powder ranges from 0.2wt% to 0.9wt%; the closed pore volume of the carbon-containing powder ranges from 0.03cm 3 / g~0.07cm 3 / g.

[0087] In a second aspect, an embodiment of the present application provides a method for preparing an electrode material, the preparation method comprising:

[0088] S101: modifying the first carbon source to obtain a modified carbon source;

[0089] S102: mixing the modified carbon source and the second carbon source and performing pretreatment to obtain a first precursor;

[0090] S103: performing oxidation treatment on the first precursor to obtain a second precursor;

[0091] S104: Sintering the second precursor to obtain carbon-containing powder as an electrode material.

[0092] In the above scheme, the mass percentage of nitrogen element ranges from 0.2wt% to 0.9wt%, the conductivity ranges from 36S / cm to 41S / cm, and the closed pore volume ranges from 0.03cm 3 / g~0.07cm 3 The combination of 200 μg and 100 μg can make the carbon-containing powder have closed pores formed by three-dimensional cross-linking of graphite crystallites.

[0093] Specifically, the sintering temperature is controlled within a certain range. If the sintering temperature is too high, it will lead to the growth of graphite crystallites, a significant decrease in nitrogen content, an increase in the degree of local graphitization of the carbon skeleton, and local contraction of the carbon matrix to produce large-sized, large-pore-volume closed pores, thereby increasing the electrical conductivity and closed pore volume; when the sintering temperature is too low, it cannot provide sufficient energy for the "conversion of open pores into closed pores", resulting in low closed pores, low electrical conductivity, and high nitrogen content. Therefore, when the aforementioned carbon-containing powder satisfies the mass percentage range of nitrogen element of 0.2wt% to 0.9wt% and the electrical conductivity is limited to 36S / cm to 41S / cm, it means that the temperature of the sintering process is in a suitable range that can balance the aforementioned pros and cons.

[0094] Meanwhile, if only the closed pore volume is high (i.e., among the three factors of mass percentage of nitrogen, conductivity and closed pore volume, only the closed pore volume is higher than the specified range), it may be due to the closed pores introduced by the process of pore formation; if the closed pore volume is low, it indicates that the carbon matrix density is high, and the carbon matrix may have a significant "soft carbonization" trend, and the closed pores are generated by the cross-linking of relatively parallel graphite microcrystals. Therefore, when the three factors are controlled within the corresponding range, it indicates that the carbon-containing powder has closed pores formed by the three-dimensional cross-linking of graphite microcrystals.

[0095] In addition, the closed pores formed by three-dimensional cross-linking of graphite microcrystals have the characteristics of small pore volume and high sodium storage activity. Therefore, they contribute to capacity performance without sacrificing compaction density. In addition, such closed pores can serve as diffusion channels for sodium ions in the carbon matrix, improve the kinetic performance, and thus contribute to fast charging and life performance; in addition, nitrogen doping improves the conductivity and wettability of the carbon matrix, inhibits polarization, and improves the kinetic performance, which can also contribute to fast charging and life performance; the closed pore volume is within a certain limit to ensure that the carbon-containing powder does not contain or contains a small amount of "pores" (caused by the decomposition of light components in the carbon source to produce gas and uneven shrinkage of the carbon skeleton), which is reflected in the improvement of compaction density performance.

[0096] For carbon-containing materials outside the above range, their closed pores are most likely not formed by three-dimensional cross-linking of graphite microcrystals. The pore size and pore volume of such closed pores are relatively large, resulting in a decrease in compaction density, and poor sodium storage activity, which leads to a weak electric field in the pore area and failure to utilize the diffusion of sodium ions in the closed pores. Therefore, the kinetic performance is poor, and the fast charging and life performance are poor.

[0097] Based on the above, it can be understood that the present application improves the electrochemical performance of the carbon-containing powder when it is ultimately used as an electrode material to make a sodium ion battery by selecting the conductivity, mass percentage of nitrogen element and closed pore volume of the carbon-containing powder.

[0098] In some embodiments of the present application, the mass percentage of nitrogen in the carbon-containing powder ranges from 0.4wt% to 0.7wt%. The closed pore volume of the carbon-containing powder ranges from 0.03cm 3 / g~0.07cm 3 / g.

[0099] It should be noted that the closed pores in the present application are not completely closed pores. The closed pores in the present application also include incompletely closed pores with gaps; helium molecules can enter and exit the closed pores through the gaps, and at the same time, other components in the sodium ion battery electrolyte except sodium ions cannot enter and exit the closed pores through the gaps. The formation method of the gap is not limited. The gap can be formed by the interlayer spacing between the carbon layers, or by the gaps, channels and other structures on the carbon matrix connected to the closed pores. The test method is detailed in the description of the test method section.

[0100] In some embodiments of the present application, the aforementioned compaction density refers to the 3T powder compaction density. Specifically, the 3T powder compaction density of the carbon-containing powder ranges from 0.95g / cm3 to 1.05g / cm3; and / or, the closed pore volume of the carbon-containing powder ranges from 0.03cm3 / g to 0.07cm3 / g; and / or, the median particle size of the carbon-containing powder ranges from 3μm to 15μm; and / or, the specific surface area of ​​the carbon-containing powder ranges from 2.0m2 / g to 10.0m2 / g.

[0101] In some embodiments of the present application, the first carbon source includes a plant carbon source.

[0102] In some embodiments of the present application, the plant carbon source is selected from at least one of coconut shell, almond shell, pistachio shell, macadamia shell, date shell, chestnut shell, hazelnut shell, peanut shell, walnut shell, peach shell, cotton, wood, bamboo, straw, and lignin.

[0103] In some embodiments of the present application, the second carbon source includes a molten carbon source.

[0104] In some embodiments of the present application, the molten carbon source includes an organic polymer carbon source and / or a sugar carbon source.

[0105] In some embodiments of the present application, the organic polymer carbon source is selected from at least one of phenolic resin, epoxy resin, melamine resin, polyfurfuryl alcohol, polyaniline, furfural resin, polyethylene glycol, polyethylene oxide, polyvinylidene fluoride, acrylic resin or polyacrylonitrile; and / or,

[0106] The carbohydrate carbon source is selected from at least one of starch, glucose, sucrose, maltose, lactose, fructose, cellulose and galactose.

[0107] In some embodiments of the present application, the first carbon source is subjected to a modification treatment to obtain a modified carbon source, comprising:

[0108] performing a first oxidation treatment on a powder of a first carbon source to obtain a first oxidation product;

[0109] The first oxidation product is subjected to a first reduction treatment to obtain a modified carbon source.

[0110] In some embodiments of the present application, the first oxidant of the first oxidation treatment is selected from at least one of nitric acid and an acid solution of nitrate; the acid solution of nitrate is obtained by dissolving nitrate in acid solution; the nitrate includes at least one of sodium nitrate, potassium nitrate, magnesium nitrate, zinc nitrate, iron nitrate, cobalt nitrate, diatomaceous nitrate, ammonium nitrate, calcium nitrate, lead nitrate, and cerium nitrate; the acid solution includes one or a combination of at least two of hydrochloric acid, hydrofluoric acid, phosphoric acid, and sulfuric acid.

[0111] In some embodiments of the present application, the oxidation temperature of the first oxidation treatment ranges from 60° C. to 80° C.; and / or,

[0112] In some embodiments of the present application, the oxidation time of the first oxidation treatment ranges from 3 hours to 24 hours.

[0113] In some embodiments of the present application, the mass concentration of nitric acid is 0.5wt% to 5.0wt%; the mass proportion of nitrate in the mixture of nitrate and acid solution is 0.5wt% to 5.0wt%.

[0114] In some embodiments of the present application, the first reducing agent of the first reduction treatment is selected from at least one of formic acid, ammonium formate, hydrazine hydrate, sodium sulfide, and sodium thiosulfate.

[0115] In some embodiments of the present application, the first catalyst of the first reduction treatment is selected from soluble salts of transition metal elements.

[0116] In some embodiments of the present application, the oxidation temperature of the first reduction treatment ranges from 60°C to 80°C.

[0117] In some embodiments of the present application, the reduction time of the first reduction treatment ranges from 3 hours to 10 hours.

[0118] In some embodiments of the present application, the mass ratio of the modified carbon source, the first reducing agent, the first catalyst, and the solvent is in the range of 1:(0.3-3):(0.1-0.2):(1.5-10). The solvent is at least one of tetrahydrofuran (THF), ethanol, benzene, isopropanol, and pure water.

[0119] In some embodiments of the present application, wherein the first carbon source is subjected to modification treatment to obtain a modified carbon source, further comprising:

[0120] The product of the first oxidation treatment is centrifuged or filtered, washed to a first pH value, and then dried;

[0121] The product of the first reduction treatment is centrifuged or filtered, washed to the second pH value, and then dried.

[0122] Among them, the first pH value range is 3 to 7; the second pH value range is 3 to 7.

[0123] In some embodiments of the present application, the modified carbon source and the second carbon source are mixed and then pretreated to obtain a first precursor, comprising:

[0124] The modified carbon source and the second carbon source are mixed and then heated and cured to obtain a cured product;

[0125] The solidified product is subjected to a pre-carbonization treatment to obtain a first precursor.

[0126] In some embodiments of the present application, the heating temperature for heat curing ranges from 100°C to 300°C.

[0127] In some embodiments of the present application, the heating time for heat curing ranges from 0.5 h to 24 h.

[0128] In some embodiments of the present application, the heating temperature of the pre-carbonization ranges from 450°C to 650°C.

[0129] In some embodiments of the present application, the heating time of pre-carbonization ranges from 0.5h to 24h.

[0130] In some embodiments of the present application, the pre-carbonization atmosphere is an inert atmosphere or an oxygen-deficient atmosphere; the inert atmosphere is selected from at least one of nitrogen atmosphere, argon atmosphere, neon atmosphere, helium atmosphere, xenon atmosphere, and krypton atmosphere; the oxygen-deficient atmosphere is a gas atmosphere with an oxygen content less than or equal to 1wt%.

[0131] In some embodiments of the present application, the modified carbon source and the second carbon source are mixed and then pretreated to obtain a first precursor, further comprising:

[0132] After the modified carbon source and the second carbon source are mixed, the mixture is subjected to a pressing process before being heated, cured and pre-carbonized;

[0133] The mass ratio of the modified carbon source to the second carbon source is 1:0.3-3.0

[0134] The pre-carbonized product is crushed and sieved.

[0135] In some embodiments of the present application, the pulverizing equipment for the pulverizing treatment is selected from at least one of a ball mill, a jet mill, a mechanical pulverizer, and a roller mill.

[0136] In some embodiments of the present application, the target median particle size of the pulverization process is 3 μm to 15 μm.

[0137] In some embodiments of the present application, the mesh size of the sieve for sieving is in the range of 30 to 325 meshes.

[0138] In some embodiments of the present application, the lamination pressure of the lamination process ranges from 10 MPa to 20 MPa.

[0139] In some embodiments of the present application, the modified carbon source and the second carbon source are mixed and then pretreated to obtain a first precursor, further comprising:

[0140] Purification treatment is performed after the pulverization treatment;

[0141] Among them, the purification process includes:

[0142] The pulverized product is mixed with an acid solution and pure water in a certain mass ratio of 1:0.1 to 1:1.5 to 10, and after stirring for a preset time, solid-liquid separation is performed to obtain a solid product; the solid product is washed to a third pH value;

[0143] The acid solution is an aqueous solution of at least one selected from hydrochloric acid, hydrofluoric acid, nitric acid, phosphoric acid and sulfuric acid; and the third pH value range is 2.5 to 4.5.

[0144] In some embodiments of the present application, the first precursor is oxidized to obtain the second precursor, comprising:

[0145] performing a second oxidation treatment on the first precursor;

[0146] Among them, the atmosphere of the first oxidation treatment is an oxidizing atmosphere, the oxidizing atmosphere includes a carrier gas and an oxidizing gas, the carrier gas is an inert gas, the inert gas includes any one of nitrogen, argon, neon, helium, xenon or krypton, or a combination of at least two; the oxidizing gas is selected from at least one of oxygen, ozone, and carbon dioxide, and the volume content of the oxidizing gas in the oxidizing atmosphere is less than or equal to 5% VOL to 30% VOL.

[0147] The temperature of the first precursor for the first oxidation treatment is 500° C. to 800° C.; the insulation time of the first oxidation treatment is 1 h to 10 h.

[0148] In some embodiments of the present application, in the step of sintering the second precursor to obtain a carbon-containing powder as an electrode material; the sintering temperature ranges from 1200°C to 1500°C; the sintering time ranges from 0.5h to 24h; the sintering atmosphere is an inert atmosphere, and the inert atmosphere is selected from at least one of nitrogen atmosphere, argon atmosphere, neon atmosphere, helium atmosphere, xenon atmosphere, and krypton atmosphere.

[0149] In a third aspect, an embodiment of the present application provides a secondary battery, comprising the aforementioned electrode material or the electrode material prepared by the preparation method.

[0150] By adopting the above scheme, according to the respective advantages and disadvantages of plant-based hard carbon and polymer (organic polymer or sugar) carbon sources for preparing hard carbon, the two are compounded, the strengths of the two are complemented, and oxidation modification is used to increase the capacity to prepare a hard carbon material with high capacity, high compaction and long life. Plant-based hard carbon has the advantages of cheap and easy to obtain carbon sources, renewable and new, and high cost performance. However, the light components of the plant-based carbon source are cracked to produce gas, and the carbon skeleton shrinks unevenly, producing a large number of "pores" with large pore size and large pore volume, resulting in low density of plant-based hard carbon. In addition, plant-based hard carbon has few inherent sodium storage sites and few sites for modification and capacity increase, making it difficult to improve capacity performance, so plant-based hard carbon often has low capacity; polymer carbon sources are rich in hydroxyl functional groups, and their pre-carbonized materials have many sites for modification and capacity increase, but the degree of stereo cross-linking between polymer hard carbon graphite crystallites is small, the internal resistance of sodium ion diffusion is large, and the kinetic performance is poor. The present invention prepares a modified carbon source through a first oxidation and a first reduction of a plant carbon source, and then mixes it with a polymer carbon source, presses it, and heats and solidifies it. The polymer carbon source molecules melt or soften, and diffuse into the gaps between the plant carbon source molecules, undergo a full cross-linking reaction with them, and synthesize a type of microstructure isomerized, high-density composite carbon source. Due to the characteristics of full cross-linking and high density of the carbon source molecules, the composite carbon source shrinks uniformly during the pre-carbonization process, inhibits the generation of "pores", reduces the pore volume, and increases the density performance. The composite carbon source-derived hard carbon graphite crystals are three-dimensionally cross-linked, the internal resistance of sodium ion diffusion inside the particles is low, and the kinetic performance is good, thereby obtaining a hard carbon negative electrode material with high compaction density, fast charging, and long life. Furthermore, a modified first carbon source having nitrogen-containing cross-linking reaction groups (-NH2, -NH-) is obtained by first performing a first oxidation and a first reduction on the first carbon source (plant carbon source), and then compounding with a second carbon source (organic polymer or sugar carbon source) to obtain a nitrogen-containing composite carbon source, thereby deriving nitrogen-doped hard carbon, thereby improving the conductivity and wettability of the hard carbon electrode, improving its kinetic properties, and improving its capacity performance.

[0151] In addition, the precarbonized material derived from plant-based carbon sources has a higher content of crystallized carbon and a lower content of amorphous carbon; the precarbonized material derived from polymer carbon sources has less crystallized carbon and more amorphous carbon; the precarbonized material derived from composite carbon sources has the characteristics of a moderate ratio of crystallized carbon and amorphous carbon, and amorphous carbon is evenly distributed among the crystallized carbon. Amorphous carbon has a higher content of sp3 hybridized carbon atoms, a small chemical bond energy, and is prone to breakage; crystallized carbon has a higher content of sp2 hybridized carbon atoms, a large chemical bond energy, and is not prone to breakage. Therefore, the composite carbon source precarbonized material is directionally etched with amorphous carbon after the second oxidation modification, and the resulting second precursor has the pore characteristics of a large number of open pores (pores connected to the interface), a small pore size (<2nm), and a uniform pore distribution. After high-temperature sintering, the open pores are transformed into closed pores with a small pore volume, which contribute to the sodium storage capacity and have high compaction density performance.

[0152] Example 1

[0153] (1) preparing a 2.5 wt% nitric acid solution, adding 1 times the weight of bamboo powder (100 mesh) to 3 times the weight of 2.5 wt% nitric acid solution, heating to 60°C under stirring, keeping warm for 24 hours, cooling, solid-liquid separation, washing with pure water to a pH of about 4, drying, and obtaining a first oxidation product; adding the first oxidation product, formic acid, ferric chloride and tetrahydrofuran in a mass ratio of 1:0.3:0.2:10, heating to 60°C under stirring, keeping warm for 5 hours, cooling, washing with pure water to a pH of about 4, drying, and obtaining a modified carbon source;

[0154] (2) The modified carbon source and phenolic resin (100 mesh) are mixed in a mass ratio of 1:0.5, pressed under a pressure of 20 MPa, and the resulting material is heated to 150°C for heat curing, kept warm for 2 hours, and cooled; the resulting material is transferred to a box furnace, heated to 450°C in a nitrogen atmosphere for pre-carbonization, kept warm for 24 hours, cooled, crushed, and gas-pulverized to a median particle size of about 5.0 μm to obtain a crushed material.

[0155] The crushed material, hydrochloric acid (concentration of 31wt%), hydrofluoric acid (concentration of 55wt%) and pure water were mixed in a mass ratio of 1:0.8:0.15:3, heated to 60°C, stirred for 24h, solid-liquid separation, washed to a pH value of 4, and dried to obtain a first precursor;

[0156] (3) The first precursor is placed in a rotary kiln, a mixed gas of carbon dioxide and nitrogen (the volume percentage of carbon dioxide is 30% VOL) ​​is introduced, the temperature is raised to 800°C for a second oxidation treatment, the temperature is kept for 3 hours, and the second precursor is cooled; (4) The second precursor is placed in a tubular furnace, the temperature is raised to 1300°C for high-temperature sintering in a nitrogen atmosphere, the temperature is kept for 4 hours, the second precursor is cooled, the VC is broken up, and the 325 mesh is sieved to obtain a carbon-containing powder of the electrode material.

[0157] Example 2

[0158] (1) Use ferric nitrate, hydrochloric acid (31wt%), and pure water in a mass ratio of 2:1:97, add hydrochloric acid and ferric nitrate to pure water in turn, stir evenly, and prepare a 2wt% ferric nitrate hydrochloric acid solution. Add 1 times the mass of litchi tree powder (100 mesh) to 5 times the mass of the above ferric nitrate hydrochloric acid solution, heat to 80°C under stirring, keep warm for 3 hours, cool, separate the solid and liquid, wash with pure water to about PH=5, and dry to obtain the first oxidation product; according to the mass ratio of the first oxidation product, ammonium formate, nickel chloride and ethanol of 1:3:0.1:6, add the first oxidation product, ammonium formate, and nickel chloride to ethanol, heat to 80°C under stirring, keep warm for 3 hours, cool, wash with pure water to about PH=7, and dry to obtain a modified carbon source;

[0159] (2) The modified carbon source and sucrose (100 mesh) are mixed in a mass ratio of 1:3, pressed under a pressure of 15 MPa, and the resulting material is heated to 100°C for heat curing, kept warm for 24 hours, and cooled; the resulting material is transferred to a box furnace, heated to 650°C in a helium atmosphere for pre-carbonization, kept warm for 0.5 hours, cooled, crushed, and gas-powdered to a median particle size of about 3.0 μm to obtain a crushed material. The crushed material, nitric acid (concentration of 50wt%) and pure water are mixed in a mass ratio of 1:0.1:1.5, heated to 70°C, stirred for 6 hours, solid-liquid separation, washed to a pH value of 4, and dried to obtain a first precursor;

[0160] (3) placing the first precursor in a rotary kiln, introducing a mixed gas of oxygen and helium (oxygen volume ratio is 10% VOL), heating to 500° C. for a second oxidation treatment, keeping the temperature for 10 hours, and cooling to obtain a second precursor;

[0161] (4) The second precursor is placed in a tube furnace, heated to 1500° C. in a krypton atmosphere for high-temperature sintering, kept at this temperature for 2 hours, cooled, broken up by VC, and sieved with 325 mesh to obtain a carbonaceous powder of the electrode material.

[0162] Example 3

[0163] (1) Magnesium nitrate, sulfuric acid (30wt%), and pure water are used in a mass ratio of 5:1:94, and hydrochloric acid and ferric nitrate are added to pure water in sequence, stirred evenly, and a 5wt% magnesium nitrate sulfuric acid solution is prepared. One times the mass of walnut shell powder (100 mesh) is added to three times the mass of the above-mentioned ferric nitrate hydrochloric acid solution, heated to 60°C under stirring, kept warm for 6 hours, cooled, solid-liquid separation, washed with pure water to about PH = 7, and dried to obtain a first oxidation product; according to the mass ratio of the first oxidation product, hydrazine hydrate, zinc sulfate and isopropanol of 1:1:0.15:1.5, the first oxidation product, hydrazine hydrate, and zinc sulfate are added to isopropanol, heated to 75°C under stirring, kept warm for 10 hours, cooled, washed with pure water to about PH = 4, and dried to obtain a modified carbon source;

[0164] (2) The modified carbon source and polyaniline (100 mesh) are mixed in a mass ratio of 1:1.5, and pressed at a pressure of 20 MPa. The resulting material is heated to 300°C for heat curing, kept warm for 0.5 hours, and cooled; the resulting material is transferred to a push plate kiln, heated to 500°C in an argon atmosphere for pre-carbonization, kept warm for 4 hours, cooled, crushed, and gas-powdered to a median particle size of about 15.0 μm to obtain a crushed material. The crushed material, nitric acid (concentration of 50wt%) and pure water are mixed in a mass ratio of 1:0.1:1.5, heated to 80°C, stirred for 6 hours, solid-liquid separation, washed to a pH value of 4.5, and dried to obtain a first precursor; obtain a first precursor;

[0165] (3) placing the first precursor in a rotary kiln, introducing a mixed gas of ozone and krypton (the volume proportion of ozone is 5% VOL), heating to 800° C. for a second oxidation treatment, keeping the temperature for 3 hours, and cooling to obtain a second precursor;

[0166] (4) The second precursor was placed in a tubular furnace, heated to 1250°C for high-temperature sintering in a nitrogen atmosphere, kept at this temperature for 6 hours, cooled, VC was broken up, and sieved through 325 mesh to obtain a carbonaceous powder of the electrode material.

[0167] Example 4

[0168] (1) Sodium nitrate, hydrofluoric acid (40 wt%), and pure water are used in a mass ratio of 0.5:1:98.5, and hydrofluoric acid and sodium nitrate are added to pure water in sequence, stirred evenly, and a 0.5 wt% sodium nitrate hydrofluoric acid solution is prepared. One times the mass of peanut shell powder (100 mesh) is added to 20 times the mass of the above-mentioned ferric nitrate hydrochloric acid solution, heated to 60°C under stirring, kept warm for 10 hours, cooled, solid-liquid separation, washed with pure water to about PH = 4, and dried to obtain the first oxidation product; the first oxidation product, sodium sulfide, cobalt sulfate and pure water are added to pure water in a mass ratio of 1:1:0.18:5, heated to 65°C under stirring, kept warm for 10 hours, cooled, washed with pure water to about PH = 7, and dried to obtain a modified carbon source;

[0169] (2) The modified carbon source and furfural resin (100 mesh) are mixed in a mass ratio of 1:0.3, pressed at a pressure of 10 MPa, and the resulting material is heated to 200°C for heat curing, kept warm for 5 hours, and cooled; the resulting material is transferred to a box furnace, heated to 550°C in a krypton atmosphere for pre-carbonization, kept warm for 2 hours, cooled, crushed, and gas-pulverized to a median particle size of about 8.0 μm to obtain a crushed material. The crushed material, sulfuric acid (concentration of 50wt%), hydrofluoric acid (concentration of 55wt%) and pure water are mixed in a mass ratio of 1:0.5:0.1:10, heated to 80°C, stirred for 6 hours, solid-liquid separation, washed to a pH value of 4.5, and dried to obtain a first precursor;

[0170] (3) placing the first precursor in a rotary kiln, introducing a mixed gas of oxygen and nitrogen (the volume proportion of oxygen is 5% VOL), heating to 800° C. for a second oxidation treatment, keeping the temperature for 5 hours, and cooling to obtain a second precursor;

[0171] (4) The second precursor is placed in a tube furnace, heated to 1500°C for high-temperature sintering in a krypton atmosphere, kept at this temperature for 0.5 h, cooled, VC broken up, and sieved with 325 mesh to obtain a carbonaceous powder of the electrode material.

[0172] Example 5

[0173] (1) Potassium nitrate, phosphoric acid (50 wt%) and pure water are used in a mass ratio of 2.5:0.5:97, and phosphoric acid and potassium nitrate are added to pure water in sequence, stirred evenly, and a 2.5 wt% potassium nitrate phosphoric acid solution is prepared. One mass of cotton straw powder (100 mesh) is added to twice the mass of the above potassium nitrate phosphoric acid solution, heated to 75°C under stirring, kept warm for 3 hours, cooled, solid-liquid separation, washed with pure water to about PH = 5, and dried to obtain a first oxidation product; the first oxidation product, sodium thiosulfate, chromium nitrate and pure water are added to pure water in a mass ratio of 1:0.6:0.12:3, heated to 65°C under stirring, kept warm for 4 hours, cooled, washed with pure water to about PH = 6, and dried to obtain a modified carbon source;

[0174] (2) The modified carbon source and corn starch (200 mesh) are mixed in a mass ratio of 1:0.8, pressed at a pressure of 20 MPa, and the resulting material is heated to 150°C for heat curing, kept warm for 3 hours, and cooled; the resulting material is transferred to a tubular furnace, heated to 600°C in a nitrogen atmosphere for pre-carbonization, kept warm for 10 hours, cooled, crushed, and gas-powdered to a median particle size of about 6.0 μm to obtain a crushed material. The crushed material, sulfuric acid (concentration of 50wt%), hydrofluoric acid (concentration of 55wt%) and pure water are mixed in a mass ratio of 1:0.3:0.1:3, heated to 75°C, stirred for 3 hours, solid-liquid separation, washed to a pH value of 4.5, and dried to obtain a first precursor;

[0175] (3) placing the first precursor in a rotary kiln, introducing a mixed gas of oxygen and nitrogen (the volume proportion of oxygen is 10% VOL), heating to 750° C. for a second oxidation treatment, keeping the temperature for 3 hours, and cooling to obtain a second precursor;

[0176] (4) The second precursor is placed in a tube furnace, heated to 1400°C in an argon atmosphere for high-temperature sintering, kept at this temperature for 24 hours, cooled, broken up by VC, and sieved with 325 mesh to obtain a carbonaceous powder of the electrode material.

[0177] Comparative Example 1

[0178] The difference between Comparative Example 1 and Example 1 is that the amount of oxidant used in step (1) is too low, that is,

[0179] Step (1) is: preparing a 0.3 wt % nitric acid solution, and the rest is the same as in Example 1.

[0180] Comparative Example 2

[0181] The difference between Comparative Example 2 and Example 1 is that the amount of oxidant used in step (1) is too much, that is,

[0182] Step (1) is: preparing 8 wt % nitric acid solution, and the rest is the same as in Example 1.

[0183] Comparative Example 3

[0184] The difference between Comparative Example 3 and Example 1 is that the amount of reducing agent used in step (1) is too low, that is,

[0185] Step (1) is: adding the first oxidation product, formic acid, ferric chloride and tetrahydrofuran in a mass ratio of 1:0.3:0.2:10, and the rest is the same as in Example 1.

[0186] Comparative Example 4

[0187] The difference between Comparative Example 4 and Example 1 is that no reducing catalyst is used in step (1), that is,

[0188] Step (1) is: adding the first oxidation product, formic acid and tetrahydrofuran in a mass ratio of 1:0.3:10, and the rest is the same as in Example 1.

[0189] Comparative Example 5

[0190] The difference between Comparative Example 5 and Example 1 is that the proportion of the first carbon source in step (2) is too high, that is,

[0191] Step (2) is: mixing the modified carbon source and thermoplastic phenolic resin (100 mesh) in a mass ratio of 1:0.3, and the rest is the same as Example 1.

[0192] Comparative Example 6

[0193] The difference between Comparative Example 6 and Example 1 is that the proportion of the first carbon source in step (2) is too low, that is,

[0194] Step (2) is: mixing the modified carbon source and thermoplastic phenolic resin (100 mesh) in a mass ratio of 1:5, and the rest is the same as Example 1.

[0195] Comparative Example 7

[0196] The difference between Comparative Example 7 and Example 1 is that the curing temperature in step (2) is too low, that is,

[0197] Step (2) is: heating the obtained material to 70°C for heat curing treatment, and keeping the temperature for 2 hours. The rest is the same as in Example 1.

[0198] Comparative Example 8

[0199] The difference between Comparative Example 8 and Example 1 is that the curing temperature in step (2) is too low or too high, that is,

[0200] Step (2) is: heating the obtained material to 400°C for heat curing treatment and keeping the temperature for 2 hours. The rest is the same as in Example 1.

[0201] Comparative Example 9

[0202] The difference between Comparative Example 9 and Example 1 is that the pre-carbonization temperature in step (2) is too low, i.e.,

[0203] Step (2) is: transferring the obtained material to a box-type furnace, heating it to 400° C. for pre-carbonization under a nitrogen atmosphere, and keeping it warm for 24 hours. The rest is the same as in Example 1.

[0204] Comparative Example 10

[0205] The difference between Comparative Example 10 and Example 1 is that the pre-carbonization temperature in step (2) is too high, i.e.,

[0206] Step (2) is: transferring the obtained material to a box-type furnace, heating it to 800° C. in a nitrogen atmosphere for pre-carbonization, and keeping it warm for 24 hours; the rest is the same as in Example 1.

[0207] Comparative Example 11

[0208] The difference between Comparative Example 11 and Example 1 is that the second oxidation temperature in step (3) is too low, that is,

[0209] Step (3) is as follows: (3) placing the first precursor in a rotary kiln, introducing a mixed gas of carbon dioxide and nitrogen (the volume percentage of carbon dioxide is 30% VOL), heating to 400°C for a second oxidation treatment, keeping the temperature for 3 hours, cooling, and obtaining a second precursor; the rest is the same as in Example 1.

[0210] Comparative Example 12

[0211] The difference between Comparative Example 12 and Example 1 is that the second oxidation temperature in step (3) is too high, that is,

[0212] Step (3) is: placing the first precursor in a rotary kiln, introducing a mixed gas of carbon dioxide and nitrogen (the volume percentage of carbon dioxide is 30% VOL), heating to 1000°C for a second oxidation treatment, keeping the temperature for 3 hours, cooling, and obtaining a second precursor; the rest is the same as in Example 1.

[0213] Comparative Example 13

[0214] The difference between Comparative Example 13 and Example 1 is that the proportion of the second oxidizing gas in step (3) is too high, that is,

[0215] Step (3) is: placing the first precursor in a rotary kiln, introducing a mixed gas of carbon dioxide and nitrogen (the volume percentage of carbon dioxide is 50% VOL), heating to 800°C for a second oxidation treatment, keeping the temperature for 3 hours, cooling, and obtaining a second precursor; the rest is the same as in Example 1.

[0216] Comparative Example 14

[0217] The difference between Comparative Example 14 and Example 1 is that the proportion of the second oxidizing gas in step (3) is too low, that is,

[0218] Step (3) is: placing the first precursor in a rotary kiln, introducing a mixed gas of carbon dioxide and nitrogen (the volume percentage of carbon dioxide is 3% VOL), heating to 800°C for a second oxidation treatment, keeping the temperature for 3 hours, cooling, and obtaining a second precursor; the rest is the same as in Example 1.

[0219] Comparative Example 15

[0220] The difference between Comparative Example 14 and Example 1 is that the sintering temperature in step (4) is too low, i.e.,

[0221] Step (4) is: the second precursor is placed in a tube furnace, heated to 1100°C for high temperature sintering in a nitrogen atmosphere, kept at this temperature for 4 hours, cooled, VC broken up, sieved with 325 mesh, and a carbonaceous powder of the electrode material is obtained. The rest is the same as in Example 1.

[0222] Comparative Example 16

[0223] The difference between Comparative Example 16 and Example 1 is that the sintering temperature in step (4) is too high, i.e.,

[0224] Step (4) is: the second precursor is placed in a tube furnace, heated to 1600°C for high temperature sintering in a nitrogen atmosphere, kept at this temperature for 4 hours, cooled, VC is broken up, and sieved with 325 mesh to obtain a carbonaceous powder of the electrode material. The rest is the same as in Example 1.

[0225] Comparative Example 17

[0226] Bamboo powder (100 mesh) was pressed under 20MPa pressure, and the obtained material was heated to 150℃ for heat curing, kept warm for 2 hours, and cooled; the obtained material was transferred to a box furnace, heated to 450℃ for pre-carbonization under nitrogen atmosphere, kept warm for 24 hours, cooled, crushed, and gas-powdered to a median particle size of about 5.0μm to obtain a crushed material. The crushed material, hydrochloric acid (concentration of 31wt%), hydrofluoric acid (concentration of 55wt%) and pure water were mixed in a mass ratio of 1:0.8:0.15:3, heated to 60℃, stirred for 24 hours, solid-liquid separation, washed to a pH value of 4, dried, placed in a tube furnace, heated to 1300℃ for high-temperature sintering under nitrogen atmosphere, kept warm for 4 hours, cooled, VC was broken up, and 325 mesh was screened to obtain a carbonaceous powder of electrode material.

[0227] Comparative Example 18

[0228] The phenolic resin (100 mesh) was pressed under a pressure of 20 MPa, and the obtained material was heated to 150°C for heat curing, kept warm for 2 hours, and cooled; the obtained material was transferred to a box furnace, heated to 450°C for pre-carbonization under a nitrogen atmosphere, kept warm for 24 hours, cooled, crushed, and gas-powdered to a median particle size of about 5.0 μm to obtain a crushed material. The crushed material, hydrochloric acid (concentration of 31wt%), hydrofluoric acid (concentration of 55wt%) and pure water were mixed in a mass ratio of 1:0.8:0.15:3, heated to 60°C, stirred for 24 hours, solid-liquid separation, washed to a pH value of 4, dried, placed in a tubular furnace, heated to 1300°C for high-temperature sintering under a nitrogen atmosphere, kept warm for 4 hours, cooled, VC was broken up, and 325 mesh was screened to obtain a carbonaceous powder of the electrode material.

[0229] The test method for this application is as follows:

[0230] (1) 3T powder compaction density (g / cm3):

[0231] The test method is: Shenzhen Sansi Zongheng Battery Powder Compacted Density Tester UTM7305 is used for testing. The sample of specified mass is placed in the mold and subjected to 3T pressure. The pressure is maintained for 30S and then released to 20N to test its thickness. According to the formula ρ=10*(m / S*H), the compacted density (unit: g / cm3) is automatically output on the instrument software.

[0232] (2) Powder conductivity test:

[0233] The test method is: the powder conductivity is tested using Mitsubishi Chemical's MCP-PD51 tester. The sample is added and tested at 20KN to obtain the conductivity data (unit S / cm).

[0234] (3) Test of median particle size:

[0235] The test method is: using MASTERSIZER3000 for testing. The particle refractive index is 2.42, the absorption rate is 1.0, the dispersant is water, and the dispersant refractive index is 1.33. The method is: weigh about 0.1g of sample in a 100mL beaker, add water to 50mL, ultrasonic for 1min, add sample to the shading degree of 8-12%, and start internal ultrasonic testing.

[0236] (4) Carbon layer spacing content test:

[0237] The test method is: using a Panalytical X'Pert PRO MPD tester, using Cu target Kα rays (wavelength λ = 0.1541nm) as the light source, and testing to obtain XRD data in the 2Theta range of 10°-90°. The carbon layer spacing is calculated by substituting the diffraction angle (002) of XRD into the Scherrer formula (unit: nm).

[0238] (5) Specific surface area test:

[0239] The test method is: using a Micrometer tester (model ASAP2460) to perform a nitrogen adsorption test at 77K to obtain the specific surface area, which is calculated using the BET formula (unit: m2 / g).

[0240] (6) SEM photo hard carbon test:

[0241] The testing method is: scanning the sample with a Hitachi Hitachi S4800 scanning electron microscope to obtain a SEM photo.

[0242] (7) True density and closed pore volume test:

[0243] The true density is tested using the Best 3H-2000TD true density meter according to the gas (helium) expansion replacement method: weigh about 3 / 4 of the sample volume in the sample pool, replace it with helium 30 times, and then use helium to measure the true density value. The closed pore volume (cm3 / g) is obtained by theoretical calculation, and the formula is:

[0244] Closed pore volume = (1 / ρ-1 / ρparam)

[0245] Where ρ is the true density of the sample (g / cm3), and ρ is the true density of the reference sample (g / cm3). It is generally believed that graphite materials are non-porous carbon materials, so artificial graphite (D50 = 8μm) is used as a reference, and ρ = 2.25cm3 / g. In the formula, the physical meaning of ρ is the density of the carbon matrix in the non-porous area of ​​the sample. Therefore, the physical meaning of "closed pore volume" is the pore volume value of "closed pores" contained in 1g of sample (cm3 / g).

[0246] (8) Test of specific capacity and initial efficiency:

[0247] The carbon-containing powder, conductive agent and binder obtained in the embodiment and comparative example were mixed in a mass percentage of 91:3:6, and the mixture was adjusted to a solid content of 50% with deionized water, coated on a single side of a copper foil current collector, dried at 130°C for 2 hours, rolled, and cut into discs with a surface density of 5.5±0.5 mg / cm2 to obtain a pole piece; glass fiber GD-120 was used as a diaphragm, a sodium sheet with a diameter of 16 mm was used as a counter electrode, 1M NaPF6 in DIGLYME=100Vol% (NP005) was used as an electrolyte, and a CR2032 battery shell was used to assemble into a button battery;

[0248] At room temperature (about 25°C), the button cell was tested on the Arbin battery test system, with the nominal specific capacity set to 300mAh / g. It was first discharged at 0.1C constant current to 1mV, then discharged at 1mV at constant voltage to a current density of 3.5*10-6A, and the discharge was cut off. After standing, it was charged at 0.1C again, with a cut-off voltage of 2V. The test results are shown in Table 2. The specific capacity (mAh / g) is the first charge capacity divided by the weight of the electrode material contained in the negative electrode sheet, and the first efficiency is the ratio of the first charge capacity to the first discharge capacity.

[0249] (9) Rate charging performance and room temperature cycle performance test:

[0250] BNH-O3A, a layered oxide made from Beite, was used as the positive electrode. The positive electrode material: conductive agent: binder were mixed in a mass ratio of 96%:2%:2%. The mixture was adjusted to a solid content of 50% with N-methylpyrrolidone, coated on both sides on an aluminum foil current collector, dried, and rolled to control the surface density to 300g / m2 to obtain a positive electrode sheet.

[0251] The carbon-containing powder, conductive agent and binder obtained in the embodiment and comparative example were mixed in a mass percentage of 91:3:6, and the mixture was adjusted to a solid content of 50% with deionized water, and coated on both sides of a copper foil current collector, dried, and rolled to a surface density of 150 g / m2 to obtain a negative electrode sheet;

[0252] The positive and negative electrodes were assembled into 554065 type soft pack batteries with an NP excess ratio of 20%, a PP separator, and 1M NaPF6 in EC:DMC:EMC=1:1:1 (volume ratio) as the electrolyte. The test voltage range was 2V-4V.

[0253] 6C / 0.2C rate charge retention rate (%) test: At room temperature, constant current charge and discharge tests were carried out at different rates of 0.2C / 0.2C and 6C / 6C, and the 6C charge capacity was divided by the 0.2C charge capacity to obtain the 6C / 0.2C rate charge retention rate;

[0254] 1C / 1C@400-week retention rate (%) test: At room temperature, a 1C / 1C constant current charge and discharge cycle test was performed. The discharge capacity at the 400th week was divided by the discharge capacity at the first week to obtain the 1C / 1C cycle 400-week retention rate.

[0255] (10) Test of nitrogen mass percentage:

[0256] The test was conducted using the German Airtech oxygen, nitrogen and hydrogen element analyzer ONH-2000. A certain mass of sample and flux (nickel foil) were added to a graphite crucible. The analysis power was set to 4.4KW, helium was used as the carrier gas, the carrier gas pressure was adjusted to 0.2-0.4MPa, and the power gas pressure was adjusted to 0.4-0.6MPa. After power was turned on, it was heated and melted, releasing N2, which was measured by a thermal conductivity cell, and the mass percentage of the nitrogen element was automatically output.

[0257] Table 1

[0258]

[0259]

[0260] Table 2

[0261]

[0262] As shown in Table 1, Table 2, Figure 2 , Figure 3 and Figure 4 As shown, the 3T powder compaction density containing the carbon-containing powder of Example 1 to Example 5 is 0.965g / cm3~1.043g / cm3, the specific capacity of the sodium ion battery is 338.5mAh / g~387.5mAh / g, the first efficiency is 92.7%~94.2%, the 6C / 0.2C charging capacity retention rate is as high as 90.2%~93.1%, and the room temperature 1C / 1C@400 cycle retention rate is 92.8%~98.1%. This shows that the carbon-containing powder provided by the present invention has the advantages of high compaction density, high capacity, high first efficiency, high rate and long cycle.

[0263] This is because the present invention modifies the plant carbon source and then compounds it with a polymer or sugar carbon source to form a composite carbon source. The composite carbon source has the characteristics of fully cross-linked carbon source molecules and high density. It shrinks uniformly during pre-carbonization, inhibits the generation of "pores", reduces the pore volume, increases density performance, and three-dimensional cross-linking occurs between graphite crystallites. The internal resistance of sodium ions diffusing inside the material particles is low, and the kinetic performance is good, thereby obtaining a hard carbon negative electrode material with high compaction density, fast charging, and long life. In addition, by first oxidizing and reducing the first carbon source (plant carbon source) to obtain a modified first carbon source with nitrogen-containing cross-linking reaction groups (-NH2, -NH-), and then compounding it with the second carbon source (organic polymer or sugar carbon source) to obtain a nitrogen-containing composite carbon source, deriving nitrogen-doped hard carbon, improving the conductivity and wettability of the hard carbon electrode, improving its kinetic performance, and improving the capacity performance.

[0264] Compared with plant-based carbon source precarbonized materials with high crystallized carbon content and less amorphous carbon, and polymer-based carbon source precarbonized materials with less crystallized carbon and more amorphous carbon, the composite carbon source precarbonized material of the present invention has the characteristics of moderate ratio of crystallized carbon and amorphous carbon content, and amorphous carbon is evenly distributed among crystallized carbon. Amorphous carbon has a high content of sp3 hybridized carbon atoms, small chemical bond energy, and is prone to breakage; crystallized carbon has a high content of sp2 hybridized carbon atoms, large chemical bond energy, and is not prone to breakage. Therefore, the present invention directs etching of amorphous carbon after the composite carbon source precarbonized material is subjected to a second oxidation modification, and the resulting second precursor has a large number of open pores (pores connected to the interface) with small pore size and uniform pore distribution. After high-temperature sintering, the open pores are transformed into closed pores with a large number, small pore volume, and uniform distribution, contributing to high capacity characteristics without sacrificing compaction density performance.

[0265] From the analysis of Example 1 and Comparative Examples 1, 3, 4, 17 and 18, it can be seen that the nitrogen content, 3T powder compaction density, powder conductivity and true density of the carbon-containing powder can be increased by performing the first oxidation and the first reduction treatment on the first carbon source, and the specific surface area can be reduced. This shows that the first oxidation and the first reduction treatment can increase the molecular crosslinking degree of the composite carbon source, promote the uniform shrinkage of its carbon matrix in the pre-carbonization stage, inhibit the generation of "pores", and increase the compaction density, powder conductivity and true density. It can also increase the three-dimensional crosslinking between its graphite crystallites, which is beneficial to the diffusion of sodium ions inside the particles and has good kinetic properties. The first oxidation and the first reduction treatment introduce nitrogen-containing groups into the composite carbon source, provide a basis for the nitrogen doping of the obtained carbon-containing powder, and further improve the capacity and kinetic properties of the carbon-containing powder. The first oxidation and the first reduction treatment improve the molecular cross-linking degree of the composite carbon source, so that the two types of carbon sources will not separate during heating, curing and pre-carbonization, thereby ensuring that the composite carbon source pre-carbonized material has a moderate ratio of crystallized carbon and amorphous carbon, and amorphous carbon is evenly distributed among the crystallized carbon. This provides a basis for the subsequent second oxidation directional etching of amorphous carbon to obtain a large number of closed pores with small pore volume and uniform distribution, which is beneficial to improving capacity performance.

[0266] Analysis of Example 1 and Comparative Example 5 and Comparative Example 6 shows that controlling the reasonable mass ratio between the modified carbon source and the second carbon source can improve the 3T powder compaction density, powder conductivity, and true density of the carbon-containing powder, reduce the closed pore volume, and help improve the capacity, rate, and cycle performance of the material. This is because if the mass ratio of the second carbon source is too high or too low, after pressing and heating and curing, the second carbon source cannot fully diffuse and modify the molecular gap of the first carbon source, and fully cross-link with it. Therefore, the molecular cross-linking degree of the obtained composite carbon source is low, the shrinkage is uneven during the pre-carbonization process, and the generation of "pores" cannot be suppressed, the density performance decreases, and the 3T powder compaction density, powder conductivity, and true density decrease. At the same time, the low molecular cross-linking degree of the composite carbon source will lead to a low cross-linking degree of graphite crystallites in the obtained carbon-containing powder, a high internal resistance of sodium ions diffusing inside the material particles, and a decrease in kinetic performance, so both the rate and cycle performance decrease. If the mass ratio of the second carbon source is too high or too low, the composite carbon source pre-carbonized material will have a high or low ratio of crystallized carbon to amorphous carbon. After the second oxidation directional etching, it will be impossible to obtain a large number of closed pores with small pore volume and uniform distribution, resulting in a decrease in capacity performance.

[0267] Analysis of Example 1 and Comparative Examples 7 and 8 shows that controlling the curing temperature within a reasonable range can improve the 3T powder compaction density, powder conductivity, and true density of the carbon-containing powder, reduce the closed pore volume, and help improve the capacity, rate, and cycle performance of the material. This is because the heating and curing temperature affects the degree of chemical crosslinking reaction and the uniformity of the reaction between the first carbon source and the second carbon source molecules modified during the heating and curing stage. If the curing temperature is too low, the "chemical crosslinking reaction" is not sufficient, the first carbon source and the second carbon source in the composite carbon source are separated, and the uneven shrinkage of the carbon matrix cannot be effectively suppressed during pre-carbonization, and the generation of "pores" cannot be suppressed; if the curing temperature is too high, the uniformity of the reaction is poor, the matrix shrinks unevenly, and the generation of "pores" cannot be suppressed. Therefore, too high or too low a curing temperature leads to a decrease in density performance, and the 3T powder compaction density, powder conductivity, and true density decrease. This results in a low degree of crosslinking of graphite crystallites in the resulting carbon-containing powder, a high internal resistance for the diffusion of sodium ions in the material particles, and a decrease in kinetic performance, so both the rate and cycle performance decrease. The curing temperature is too high or too low, resulting in uneven distribution of crystallized carbon and amorphous carbon content in the pre-carbonized material particles of the composite carbon source, causing the amorphous carbon content to be locally high. After the second oxidation, larger pores are generated in the area where the amorphous carbon is concentrated. Some large-diameter pores are difficult to form closed pores through sintering, resulting in a decrease in capacity performance.

[0268] From the analysis of Example 1 and Comparative Examples 2, 9 and 10, it can be known that controlling the pre-carbonization temperature within a reasonable range can improve the 3T powder compaction density of the carbon-containing powder, which is beneficial to improving the capacity, rate and cycle performance of the material. This is because, if the mass concentration of the oxidant in the first oxidation stage is too high and the degree of oxidation is too high, the modified carbon source will become porous, and then the pre-carbonized material will become loose and porous. If the pre-carbonization temperature is too low, the pre-carbonized material will be loose and porous, and will be significantly etched after the second oxidation. Some pores are difficult to convert into closed pores, resulting in a decrease in the compaction density and powder conductivity of the obtained carbon-containing powder, an increase in the specific surface area, and a decrease in the kinetic properties, so the rate and cycle performance decrease. If the pre-carbonization temperature is too high, the texture of the pre-carbonized material will be too dense, which is not conducive to the directional etching of amorphous carbon by the second oxidation, and the capacity increase will fail;

[0269] From the analysis of Example 1 and Comparative Examples 11, 12, 13 and 14, it can be seen that controlling the first oxidation degree, the second oxidation temperature and the proportion of the second oxidation gas within a reasonable range is beneficial to improving the 3T powder compaction density of the carbon-containing powder and improving the capacity performance of the material. This is because, if the second oxidation temperature is too low or the proportion of the second oxidation gas is too low, the effect of the second oxidation directional etching of amorphous carbon will be weakened, and the number of open pores (pores connected to the interface) with small pore size and uniform pore distribution in the obtained second precursor will be reduced. After high-temperature sintering, the number of closed pores with small pore volume and uniform distribution transformed from open pores will be reduced, and the capacity will decrease; if the second oxidation temperature is too high or the proportion of the second oxidation gas is too high, the pre-carbonized material will be over-etched, and the carbon matrix will form open pores with large pore size, large pore volume and uneven distribution. Some of the open pores will be converted into closed pores after high-temperature sintering. The volume sodium storage utilization rate of these closed pores is low (sodium is filled on the surface of the pore wall, and there is no sodium storage activity in the center area of ​​the pore), resulting in a decrease in capacity performance. Some of the open pores will remain open pores after high-temperature sintering, which will lead to an increase in specific surface area, an increase in defect sites, and an increase in side reactions, thereby resulting in a decrease in the compaction density and capacity, rate and cycle performance of the 3T powder.

[0270] Analysis of Example 1 and Comparative Examples 15 and 16 shows that controlling the sintering temperature within a reasonable range is beneficial to improving the capacity, rate and cycle performance of the carbon-containing powder. This is because when the sintering temperature is too low, the opening of the second precursor is not enough to form closed pores, the closed pore volume of the obtained carbon-containing powder is low, the pore sodium storage capacity is low, and the sintering temperature is too low, resulting in low powder conductivity, large polarization of the obtained carbon-containing powder, and decreased rate and cycle performance; when the sintering temperature is too high, the carbon interlayer spacing of the hard carbon drops sharply, and the sodium storage sites between the carbon layers decrease, resulting in a decrease in the sodium storage capacity between the carbon layers, an increase in the closed pore volume and pore size, but the closed pore volume sodium storage utilization rate is low (sodium is filled on the surface of the pore wall, and there is no sodium storage activity in the center area of ​​the pore), and the pore sodium storage capacity is reduced, so the capacity performance decreases. As the carbon interlayer spacing drops sharply, the steric hindrance of the diffusion of sodium ions in the obtained carbon-containing powder increases significantly, and the rate and cycle performance decrease.

[0271] Analysis of Example 1 and Comparative Examples 17 and 18 shows that by controlling the sintering temperature within a reasonable range, the carbon-containing powder obtained by the present invention has significant advantages in 3T powder compaction density, capacity, rate, and cycle performance compared to a single first carbon source-derived hard carbon or a second carbon source-derived hard carbon. This is because the present invention prepares hard carbon based on the respective advantages and disadvantages of plant-based hard carbon and polymer (organic polymer or sugar) carbon sources, composites the two, and complements each other, supplemented by nitrogen doping and oxidation modification to increase capacity, to prepare a hard carbon negative electrode material with high capacity, high compaction, fast charging, and long life performance. A single first carbon source-derived hard carbon or a second carbon source-derived hard carbon cannot achieve the technical effect of the present invention. Figures 2 to 4It is shown that the carbon-containing powder provided by the present invention has better capacity, rate and cycle performance than the carbon-containing powder directly prepared from a single carbon source. Figure 5 It shows that the carbon-containing powder provided by the present invention has no "pores" on the surface and inside, while the carbon-containing powder of Comparative Example 17 has "pores" on the surface and inside, and the 3T powder compaction density of the former is higher than that of the latter. This shows that the composite carbon source has the characteristics of fully cross-linked carbon source molecules and high density, and shrinks uniformly during pre-carbonization, which can play a technical effect of inhibiting the generation of "pores" and reducing pore volume.

[0272] The technical solutions provided by the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of ​​the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. An electrode material for use in a sodium ion battery, characterized in that: The electrode material includes: carbonaceous powder; The conductivity of the carbon-containing powder is in the range of 36S / cm to 41S / cm; the mass percentage of nitrogen in the carbon-containing powder is in the range of 0.2wt% to 0.9wt%; the closed pore volume of the carbon-containing powder is in the range of 0.03cm 3 / g~0.07cm 3 / g.

2. The electrode material according to claim 1, characterized in that: in, The mass percentage of nitrogen in the carbon-containing powder ranges from 0.4wt% to 0.7wt%.

3. The electrode material according to claim 1 or 2, characterized in that: in, The compacted density of the carbon-containing powder is in the range of 0.95 g / cm 3 ~1.05g / cm 3 ; And / or, the carbon interlayer spacing of the electrode material ranges from 0.37 nm to 0.39 nm; And / or, the median particle size of the carbon-containing powder is in the range of 3 μm to 15 μm; And / or, the specific surface area of ​​the carbon-containing powder is in the range of 2.0 m 2 / g~10.0m 2 / g.

4. A method for preparing an electrode material, characterized in that: The preparation method comprises: Modifying the first carbon source to obtain a modified carbon source; The modified carbon source and the second carbon source are mixed and pretreated to obtain a first precursor; The first precursor is subjected to oxidation treatment to obtain a second precursor; sintering the second precursor to obtain a carbonaceous powder as the electrode material; The conductivity of the carbon-containing powder is in the range of 36S / cm to 41S / cm; the mass percentage of nitrogen in the carbon-containing powder is in the range of 0.2wt% to 0.9wt%; the closed pore volume of the carbon-containing powder is in the range of 0.03cm 3 / g~0.07cm 3 / g.

5. The preparation method according to claim 4, characterized in that: in, The first carbon source includes a plant carbon source; And / or, the second carbon source includes a carbon source having a melting point and / or a softening point.

6. The preparation method according to claim 4, Features: Wherein, the modifying the first carbon source to obtain a modified carbon source comprises: performing a first oxidation treatment on the powder of the first carbon source to obtain a first oxidation product; The first oxidation product is subjected to a first reduction treatment to obtain the modified carbon source.

7. The preparation method according to claim 6, characterized in that: The first oxidant used for the first oxidation treatment is selected from at least one of nitric acid and nitrate acid solution; the nitrate acid solution is obtained by dissolving nitrate in acid solution; the nitrate includes at least one of sodium nitrate, potassium nitrate, magnesium nitrate, zinc nitrate, iron nitrate, cobalt nitrate, nitrate, ammonium nitrate, calcium nitrate, lead nitrate, and cerium nitrate; the acid solution includes one or a combination of at least two of hydrochloric acid, hydrofluoric acid, phosphoric acid, and sulfuric acid; And / or, the oxidation temperature of the first oxidation treatment ranges from 60°C to 80°C; And / or, the oxidation time of the first oxidation treatment ranges from 3h to 24h; And / or, the mass concentration of the nitric acid is 0.5wt% to 5.0wt%; the mass proportion of nitrate in the nitrate acid solution is 0.5wt% to 5.0wt%; the ratio of the mass of the first carbon source to the mass of the first oxidant solution is in the range of 2 to 20; and / or, the first reducing agent of the first reduction treatment is selected from at least one of formic acid, ammonium formate, hydrazine hydrate, sodium sulfide, and sodium thiosulfate; and / or, the first catalyst of the first reduction treatment is selected from soluble salts of transition metal elements; And / or, the temperature of the first reduction treatment ranges from 60°C to 80°C; And / or, the reduction time of the first reduction treatment ranges from 3h to 10h; And / or, the mass ratio of the first oxidation product, the first reducing agent, the first catalyst, and the solvent is in the range of 1:(0.3-3):(0.1-0.2):(1.5-10); And / or, the solvent is at least one of tetrahydrofuran, ethanol, benzene, isopropanol and pure water.

8. The preparation method according to claim 6, Features: Wherein, the step of modifying the first carbon source to obtain a modified carbon source further comprises: The product of the first oxidation treatment is centrifuged or filtered, washed to a first pH value, and then dried; and / or, centrifuging or filtering the product of the first reduction treatment, washing it to the second pH value, and then drying it; Among them, the first pH value range is 3-7; the second pH value range is 3-7.

9. The preparation method according to claim 4, Features: The step of mixing the modified carbon source with the second carbon source and then pretreating the mixture to obtain the first precursor comprises: The modified carbon source and the second carbon source are mixed and then heated and cured to obtain a cured product; The solidified product is subjected to a pre-carbonization treatment to obtain a first precursor.

10. The preparation method according to claim 9, characterized in that: in, The heating temperature of the heating curing is in the range of 100°C to 300°C; And / or, the heating time of the heating curing is in the range of 0.5h to 24h; And / or, the pre-carbonization heating temperature is in the range of 450°C to 650°C; And / or, the pre-carbonization heating time ranges from 0.5h to 24h; And / or, the pre-carbonization atmosphere is an inert atmosphere or an oxygen-deficient atmosphere; And / or, the inert atmosphere is selected from at least one of nitrogen atmosphere, argon atmosphere, neon atmosphere, helium atmosphere, xenon atmosphere, and krypton atmosphere; And / or, the oxygen-deficient atmosphere is a gas atmosphere with an oxygen content of less than or equal to 1 wt %.

11. The preparation method according to claim 10, Features: Wherein, the mixing of the modified carbon source and the second carbon source and pretreatment to obtain the first precursor further comprises: After the modified carbon source and the second carbon source are mixed, the mixture is subjected to a pressing process before being heated, cured and pre-carbonized; The mass ratio of the modified carbon source to the second carbon source is 1:(0.3-3.0); The pre-carbonized product is crushed and sieved; The pulverizing equipment used in the pulverizing process is selected from at least one of a ball mill, a jet mill, a mechanical pulverizer, and a roller mill; and / or, the target median particle size of the pulverization process is 3 μm to 15 μm; And / or, the mesh size of the sieve for the sieving process ranges from 30 mesh to 325 mesh; And / or, the pressing pressure of the pressing process is in the range of 10 MPa to 20 MPa.

12. The preparation method according to claim 11, characterized in that: in, The method of mixing the modified carbon source with the second carbon source and then pretreating the mixture to obtain the first precursor further comprises: Performing a purification process after the pulverization process; Wherein, the purification process comprises: The pulverized product is mixed with an acid solution and pure water in a certain mass ratio of 1:(0.1-1):(1.5-10), and after stirring for a preset time, solid-liquid separation is performed to obtain a solid product; washing the solid product to a third pH value; The acid solution is an aqueous solution of at least one selected from hydrochloric acid, hydrofluoric acid, nitric acid, phosphoric acid and sulfuric acid; and the third pH value ranges from 2.5 to 4.

5.

13. The preparation method according to claim 4, characterized in that: in, The step of subjecting the first precursor to oxidation treatment to obtain the second precursor comprises: performing a second oxidation treatment on the first precursor; The atmosphere of the second oxidation treatment is an oxidizing atmosphere, which includes a carrier gas and an oxidizing gas, wherein the carrier gas is an inert gas, including any one of nitrogen, argon, neon, helium, xenon or krypton, or a combination of at least two thereof; the oxidizing gas is selected from at least one of oxygen, ozone, air and carbon dioxide, and the volume content of the oxidizing gas in the oxidizing atmosphere is 5%VOL to 30%VOL; The temperature of the first oxidation treatment of the first precursor is 500° C. to 800° C.; the holding time of the first oxidation treatment is 1 h to 10 h.

14. The preparation method according to claim 4, characterized in that: in, In the step of sintering the second precursor to obtain the carbon-containing powder as the electrode material; the sintering temperature ranges from 1200°C to 1500°C; the sintering time ranges from 0.5h to 24h; the sintering atmosphere is an inert atmosphere, and the inert atmosphere is selected from at least one of nitrogen atmosphere, argon atmosphere, neon atmosphere, helium atmosphere, xenon atmosphere, and krypton atmosphere.

15. An electrode, characterized in that: The electrode comprises the electrode material according to any one of claims 1 to 3 or the electrode material prepared by the preparation method according to any one of claims 4 to 14.

16. A secondary battery, characterized in that: The secondary battery comprises the electrode material according to any one of claims 1 to 3 or the electrode material prepared by the preparation method according to any one of claims 4 to 14 or the electrode according to claim 15.